Effectiveness of Mango Gedong Gincu Peel Extract Gel (Mangifera indica L.) on Cut Wounds in Male Wistar White Rats (Rattus norvegicus) - Fathunnisa, Firda; Marfuati, Sri; Fitriani, Hikmah (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2024)
Background: A wound is an injury to a part of the body where the skin and the underlying tissue lose continuity. The wound healing is a complex process consisting inflammatory phase, proliferation phase, and maturation phase. Open wounds often occur in everyday life and if left behind and untreated can potentially lead to bacterial infection. Mango gedong gincu peel extract (Mangifera indica L.) contains flavonoids, tannins, phenols, triterpenoids, steroids, alkaloids, and saponins which have roles in wound healing. Aims: To analyses the effectiveness of mango gedong gincu peel extract gel (Mangifera indica L.) against the healing of cut wounds in male wistar white rats (Rattus norvegicus). Methods: The study was an experimental study with a post-test only control group design using 25 male wistar white rat as the subject and was carried out in the FK UGJ Research Laboratory. The study used five groups : negative control group, positive control group, and treatment group using mango gedong gincu peel extract gel (Mangifera indica L.) with concentrations of 5%, 10%, and 15%. Results: The results of the study revealed that mango (Mangifera indica L.) gedong gincu peel is a source of various phytochemical such as flavonoids, tannins, phenols, triterpenoids, steroids, alkaloids, and saponins. This study showed that the 5% and 10% concentration treatment groups had the same average length measurement wound of 0.86 cm. The fastest observation of erythema was the 5% concentration group with a healing rate of 8 days, in the observation of edema the 10% concentration group was the fastest of 6 days, and the observation long of healing time was 5% and 10% concentration had the same rate of 11 days. Conclusion: Mango gedong gincu peel extract gel (Mangifera indica L.) was effective against wound healing with optimum concentrations of 5% and 10% which gives the best healing effect against wounds in male wistar white rats (Rattus norvegicus). Received: 25 September 2024 | Reviewed: 22 October 2024 | Revised: 05 November 2024 | Accepted: 09 November 2024.